2022
DOI: 10.2337/db21-0506
|View full text |Cite
|
Sign up to set email alerts
|

Methazolamide Attenuates the Development of Diabetic Cardiomyopathy by Promoting β-Catenin Degradation in Type 1 Diabetic Mice

Abstract: Methazolamide (MTZ), a carbonic anhydrase inhibitor, has been shown to inhibit cardiomyocyte hypertrophy and exert a hypoglycemic effect in patients with type 2 diabetes mellitus and diabetic db/db mice. However, whether MTZ has a cardioprotective effect in the setting of diabetic cardiomyopathy is not clear. We investigated the effects of MTZ in a mouse model of streptozotocin-induced type 1 diabetes mellitus (T1DM). Diabetic mice received MTZ by intragastric gavage (10, 25, or 50 mg/kg; daily for 16 weeks). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The activation of canonical WNT and simultaneous removal of intracellular contacts synergistically stimulate cardiomyocyte proliferation. 172 The reactivation of WNT/β-catenin signaling occurs under different pathological conditions, such as (i) hypertensive heart disease, 79,173,174 (ii) diabetic cardiomyopathy, [175][176][177][178] (iii) heart failure that is caused by ischemic disease and myocardial infarction, 179,180 and (iv) autoimmune myocarditis. 181 Acute reactivation of the βcatenin signaling pathway via the adenovirus-mediated overexpression of constitutively active βcatenin is cardioprotective after myocardial infarction, reducing scar size, decreasing apoptosis, and improving contractile properties.…”
Section: Canonical Wnt Pathway In Postnatal Heart Growth and Heart Re...mentioning
confidence: 99%
See 2 more Smart Citations
“…The activation of canonical WNT and simultaneous removal of intracellular contacts synergistically stimulate cardiomyocyte proliferation. 172 The reactivation of WNT/β-catenin signaling occurs under different pathological conditions, such as (i) hypertensive heart disease, 79,173,174 (ii) diabetic cardiomyopathy, [175][176][177][178] (iii) heart failure that is caused by ischemic disease and myocardial infarction, 179,180 and (iv) autoimmune myocarditis. 181 Acute reactivation of the βcatenin signaling pathway via the adenovirus-mediated overexpression of constitutively active βcatenin is cardioprotective after myocardial infarction, reducing scar size, decreasing apoptosis, and improving contractile properties.…”
Section: Canonical Wnt Pathway In Postnatal Heart Growth and Heart Re...mentioning
confidence: 99%
“…175,176 The inhibition of βcatenin ameliorates the severity of heart failure. 178 The former mechanism was determined in colorectal cancer. High glucose concentrations lead to an increase in the O-GlcNAcylation of βcatenin at different sites, and Thr41 is the most important site for protein stability and transcriptional activity because of competition with GSK3β for phosphorylation.…”
Section: Inter Con Nec Tions Between Wnt/β-catenin Pathway and Glucos...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed to be related to oxidative stress, inflammation, myocardial apoptosis, autophagy and mitochondrial damage (Avagimyan et al, 2022). Many researchers have confirmed that β-catenin is involved in the development of DCM (Xi et al, 2015;Liu et al, 2020;Chen et al, 2022). In the DCM model induced by streptozotocin (STZ), the protein and mRNA expression levels of Wnt2, β-catenin, and c-Myc were increased in a time-dependent manner, as well as the expression of p-GSK3β (Xi et al, 2015).…”
Section: β-Catenin and Diabetic Cardiomyopathiesmentioning
confidence: 99%
“…A previous study demonstrated that they were divided into six groups with or without luteolin (5, 10, and 20 µM) and HGI-induced (glucose at 25.5 mM and insulin at 0.1 µM) for 48 h. The Con group was treated with corresponding amount of mannitol. All cells were cultured at 37°C with 5% CO 2 [15,22,27,28].…”
Section: Primary Culture Of Nrcmsmentioning
confidence: 99%